1979
DOI: 10.1002/jcp.1040980310
|View full text |Cite
|
Sign up to set email alerts
|

Ordered replication of DNA sequences: Synthesis of mouse satellite and adjacent main band sequences

Abstract: The replication of mouse satellite DNA was delayed when synchronized 3T3 cells were exposed to low concentrations of hydroxyurea during S phase, It appears that the onset of satellite replication is not a time dependent event, but instead requires that a certain amount of main band DNA be synthesized first. Using hydroxyapatite chromatography and S1 nuclease digestion, a procedure was developed to quantitate the synthesis of both satellite and neighboring main band sequences. The replication kinetics of satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Nonetheless, activation of all origins at the onset of the S phase cannot be excluded. For example, the replication time of a given DNA sequence could be determined by the distance (5,10) and, perhaps, by the presence of attenuation barriers traversed by a replication fork activated at the onset of the S phase. More information about the structure, function, genomic distribution, and nuclear location of individual and groups of replication origins will be required to examine these ideas.…”
mentioning
confidence: 99%
“…Nonetheless, activation of all origins at the onset of the S phase cannot be excluded. For example, the replication time of a given DNA sequence could be determined by the distance (5,10) and, perhaps, by the presence of attenuation barriers traversed by a replication fork activated at the onset of the S phase. More information about the structure, function, genomic distribution, and nuclear location of individual and groups of replication origins will be required to examine these ideas.…”
mentioning
confidence: 99%
“…DNA replication proceeds bidirectionally within each replicon from an origin until reaching replication forks proceeding outward from adjacent origins of replication (24,28) . Groups of replicons are activated in a defined temporal order that is maintained from one S-phase to the next (1,11,39,40,45,47) . Clusters of replicons initiate replication in synchrony and are similar in size and rate of fork movement (21,27) .…”
mentioning
confidence: 99%
“…In particular, it has been observed that heterochromatic chromosomal regions are usually the last to complete replication. These include the inactive X chromosome in females (facultative heterochromatin [8,18,36]) and centromeric regions (constitutive heterochromatin [11,16]). The darkly staining Gpositive bands produced by Giemsa staining procedures contain DNA that replicates late during S-phase, whereas Gnegative regions contain DNA that replicates predominantly during the first half of S-phase (9,12,15,30,35,38,46) .…”
mentioning
confidence: 99%